Microbial Safety, Visual Quality and Consumers’ Perception of Minimally- Processed Ready-to-eat Salad Vegetables Prepared and Stored at Room and Refrigeration Temperature - Uddin, Md Nazim; Zaman, Sharmin; Aziz, Ashfaq; Yamamoto, Kazutaka; Nakaura, Yohiko; Bari, Md Latiful (Bangladesh Journal of Microbiology, 2022)
Raw salad vegetables are evaluated for the consumer’s perceptions on taking ready to eat fresh cut-vegetables and the effectiveness of some non-chlorine disinfectants [peracetic acid (PAA), shell powder (SP) and hydrogen peroxide (H2O2)] in improving the microbial safety, quality and shelf life of ready to eat fresh-cut vegetables (lettuce, carrot and cucumber) at ambient and refrigeration temperature. Consumer’s perception study results identified three clusters of consumers, whose preferences are related to purchasing styles and socio-demographic variables.The overall positive attitude of consumers was evident towards convenience, taste and appearance, but safety and health benefit attributes get importance while buying the ready to eat fresh-cut vegetables.The microbiological and visual observation result demonstrated that, all the non-chlorine sanitizers used were able to decrease the bacterial population in fresh-cut vegetables initially; however, microbial population increases or remain constant or decrease depending on the types of vegetables, storage temperature and duration. In addition, among the wash-sanitizers, PAA and H2O2 showed better microbial reduction for fresh-cut lettuce, and cucumber, and SP showed better microbial reduction for fresh-cut carrot. Irrespective of sanitizer treatment refrigerated storage showed better visual quality, microbial safety and shelf life of fresh-cut produce. Therefore, this study results suggested that washing fresh-cut vegetables with produce specific sanitizer and stored at refrigerated temperature keep the quality of fresh-cut produce better compared to ambient storage. Bangladesh J Microbiol, Volume 38, Number 2, December 2021, pp 51-62